Engineering Design Process (EDP)-Based Learning to Enhance High School Students' Creativity in Alternative Energy Topics - Ujang Sudrajat; Didit Ardianto; Anna Permanasari (Postgraduate, University of Mataram, 2023)
The energy issue is one of the 17 Sustainable Development Goals (SDGs), which is a global development agenda that all countries, including Indonesia, must follow. The curriculum plays a crucial role in enhancing students' energy literacy. It is expected that with the energy literacy possessed by students, they will have a good understanding of energy, which will encourage them to use energy wisely. Additionally, it is hoped that creative ideas from students will emerge to address energy-related problems. Based on this background, this research aims to enhance students' creativity in addressing energy issues. The research method employed is a quantitative research method with a Pretest-Posttest Nonequivalent Control Group Design, which is a form of Quasi Experimental Design. The subjects in this study are twelfth-grade science students (XII MIPA) selected through purposive sampling and divided into two groups, namely the control group and the experimental group. The control group uses a project-based learning model, while the experimental group uses project-based learning based on the engineering design process. The number of samples for the experimental group is 33 students, and for the control group, it is 34 students, making a total of 67 research subjects. The creative thinking skills of students are measured using a descriptive test that includes indicators of creative thinking skills, while student creativity in their products is measured using an assessment sheet for creative products based on presentations and testing of creative products carried out at the end of the learning process. The data analysis results show that there is an improvement in students' creative thinking skills, as indicated by the average N-Gain achievement of 53.3%, falling into the moderate category. Additionally, the creativity of student products in all creative product indicators is rated as highly creative, with an average score of 89. The Mann Whitney U Test results indicate a significant difference in the improvement of creative thinking skills and student creativity in their products